2020
DOI: 10.1038/s41571-020-0392-0
|View full text |Cite
|
Sign up to set email alerts
|

ctDNA applications and integration in colorectal cancer: an NCI Colon and Rectal–Anal Task Forces whitepaper

Abstract: An increasing number of studies are describing potential uses of circulating tumour DNA (ctDNA) in the care of patients with colorectal cancer. Owing to this rapidly developing area of research, the Colon and Rectal–Anal Task Forces of the United States National Cancer Institute convened a panel of multidisciplinary experts to summarize current data on the utility of ctDNA in the management of colorectal cancer and to provide guidance in promoting the efficient development and integration of this technology in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
225
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(251 citation statements)
references
References 117 publications
(142 reference statements)
5
225
0
1
Order By: Relevance
“…The proportion of CRC patients in whom ctDNA can be identified depends on the tumor volume and ranges from 50% to 90% in those with non-metastatic or metastatic disease, respectively [ 76 ]. There is evidence that after CRC curative resection, the detection rate of ctDNA could range from 8–15% in stage II to 50% in stage IV [ 31 , 32 , 77 ]. Serum DNA concentrations and integrity index may play an important role not only in early complementary diagnosis but also in monitoring of progression and prognosis of CRC.…”
Section: Clinical Utility Of Liquid Biopsies In Patients With Colomentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of CRC patients in whom ctDNA can be identified depends on the tumor volume and ranges from 50% to 90% in those with non-metastatic or metastatic disease, respectively [ 76 ]. There is evidence that after CRC curative resection, the detection rate of ctDNA could range from 8–15% in stage II to 50% in stage IV [ 31 , 32 , 77 ]. Serum DNA concentrations and integrity index may play an important role not only in early complementary diagnosis but also in monitoring of progression and prognosis of CRC.…”
Section: Clinical Utility Of Liquid Biopsies In Patients With Colomentioning
confidence: 99%
“…Limitations of NGS, principally with regard to the overall clinical sensitivity, could be overtaken implementing NGS with mutant allele enrichment or using digital PCR to improve reliability [ 96 , 114 ]. Mass-spectrometry and Real-Time PCR are other promising techniques for ctDNA assessment, which are rapid and cheap, require small quantities of input material, and have high sensitivity and specificity [ 77 , 115 ]. If possible, ctDNA should be analyzed in combination with CTCs and exosomal miRNAs, to obtain as much data as possible from a single blood sample [ 116 ].…”
Section: Current Issues and Limitations Of Liquid Biopsymentioning
confidence: 99%
“…Although promising, ct-DNA based profiling of BTC has several limitations related to the technology itself and its applicability. Wide variations exist in the preanalytical variables, assay characteristics (PCR-based versus NGS-based techniques), bioinformatic analysis methods, sensitivity, and specificity [40]. These factors pose significant challenges in the interpretation of clinical trial data utilizing different ctDNA platforms.…”
Section: Circulating Tumor Dna (Ctdna)-based Molecular Profilingmentioning
confidence: 99%
“…The study result showed an error rate that would have implications for clinical decision-making [ 70 ]. Recently the Colon and Rectal–Anal Task Forces of the United States National Cancer Institute has published a whitepaper providing detailed guidance in standardization and efficient development of the ctDNA technology [ 71 ].…”
Section: Future Perspective and Conclusionmentioning
confidence: 99%